2013
DOI: 10.1007/s11251-013-9280-7
|View full text |Cite
|
Sign up to set email alerts
|

The benefit of being naïve and knowing it: the unfavourable impact of perceived context familiarity on learning in complex problem solving tasks

Abstract: The nal publication is available at Springer via http://dx.doi.org/10.1007/s11251-013-9280-7.Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 32 publications
2
29
0
Order By: Relevance
“…In addition to the debate about intelligence’s contribution to complex problem solving, many researchers have pointed out the significance of knowledge for the successful control of complex systems (e.g., Bainbridge, 1974; Dörner et al, 1983; Chi et al, 1988; Goode and Beckmann, 2010; Beckmann and Goode, 2014). Expert knowledge is sometimes claimed to be the only important predictor of real-life problem solving success (Ceci and Liker, 1986), while others point out that both intelligence and knowledge contribute substantially to predicting job performance (Schmidt, 1992), which certainly includes complex problem solving.…”
Section: Part I: Empirical Investigation Of the Cognitive Prerequisitmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the debate about intelligence’s contribution to complex problem solving, many researchers have pointed out the significance of knowledge for the successful control of complex systems (e.g., Bainbridge, 1974; Dörner et al, 1983; Chi et al, 1988; Goode and Beckmann, 2010; Beckmann and Goode, 2014). Expert knowledge is sometimes claimed to be the only important predictor of real-life problem solving success (Ceci and Liker, 1986), while others point out that both intelligence and knowledge contribute substantially to predicting job performance (Schmidt, 1992), which certainly includes complex problem solving.…”
Section: Part I: Empirical Investigation Of the Cognitive Prerequisitmentioning
confidence: 99%
“…Nevertheless, the MCS tasks are very similar to each other and implement only a small number of CPS characteristics, giving the subtests high internal consistencies. Specifically, all minimal systems can be fully explored with the simple strategy “vary one thing at a time” (VOTAT; e.g., Vollmeyer et al, 1996) or the closely related strategy “vary one or none at a time” (Beckmann and Goode, 2014; for additional distinctions see Lotz et al, 2017). No special training is necessary to learn these strategies.…”
Section: Part Ii: Review and Critique Of The Minimally Complex Systemmentioning
confidence: 99%
“…Numerous articles on the subject have been published in recent years, documenting the increasing research activity relating to this field. In the following collection of papers we list only those published in 2010 and later: theoretical papers (Blech and Funke, 2010; Funke, 2010; Knauff and Wolf, 2010; Leutner et al, 2012; Selten et al, 2012; Wüstenberg et al, 2012; Greiff et al, 2013b; Fischer and Neubert, 2015; Schoppek and Fischer, 2015), papers about measurement issues (Danner et al, 2011a; Greiff et al, 2012, 2015a; Alison et al, 2013; Gobert et al, 2015; Greiff and Fischer, 2013; Herde et al, 2016; Stadler et al, 2016), papers about applications (Fischer and Neubert, 2015; Ederer et al, 2016; Tremblay et al, 2017), papers about differential effects (Barth and Funke, 2010; Danner et al, 2011b; Beckmann and Goode, 2014; Greiff and Neubert, 2014; Scherer et al, 2015; Meißner et al, 2016; Wüstenberg et al, 2016), one paper about developmental effects (Frischkorn et al, 2014), one paper with a neuroscience background (Osman, 2012) 1 , papers about cultural differences (Güss and Dörner, 2011; Sonnleitner et al, 2014; Güss et al, 2015), papers about validity issues (Goode and Beckmann, 2010; Greiff et al, 2013c; Schweizer et al, 2013; Mainert et al, 2015; Funke et al, 2017; Greiff et al, 2017, 2015b; Kretzschmar et al, 2016; Kretzschmar, 2017), review papers and meta-analyses (Osman, 2010; Stadler et al, 2015), and finally books (Qudrat-Ullah, 2015; Csapó and Funke, 2017b) and book chapters (Funke, 2012; Hotaling et al, 2015; Funke and Greiff, 2017; Greiff and Funke, 2017; Csapó and Funke, 2017a; Fischer et al, 2017; Molnàr et al, 2017; Tobinski and Fritz, 2017; Viehrig et al, 2017). In addition, a new “Journal of Dynamic Decision Making” (JDDM) has been launched (Fischer et al, 2015, 2016) to give the field an open-access outlet for research and discussion.…”
mentioning
confidence: 99%
“…With the diffuse and uncertain aim of finding out how the scenario works, the mind looks for familiar anchors and System 1 "intuitively" suggests topics or problems that fit this criteria. Beckmann and Goode (2014) found out, however, that such "false familiarity" -vague but in no way perfect knowledge that is triggered by the semantic meaning of a certain system variable -has detrimental effects on knowledge acquisition. Existing assumptions are taken as correct and are not systematically tested, thus leading to a faulty or incomplete mental model of the scenario.…”
Section: Typical Errors When Dealing With Complex Systemsmentioning
confidence: 98%
“…On the other hand, if very general and abstract scenarios are used for training, domaingeneral principles might be demonstrated but their usefulness for domain-specific situations might be questionable. In addition, Beckmann and Goode (2014) pointed out that scenarios which use meaningful labels for the included variables, thus being "semantically embedded", Studies on the training of systems thinking and complex problem solving are still scarce and produced mixed results. Krétzschmar and Süß (2015) showed that university students were able to extract general principles of system exploration by just interacting with several, heterogeneous scenarios over a certain amount of time.…”
Section: Adapting Educational Curriculamentioning
confidence: 99%